J‐Integral from Full Field Kinematic Data for Natural Rubber Compounds. (18th August 2015) - Caimmi, F.; Calabrò, R.; Briatico‐Vangosa, F.; Marano, C.; Rink, M.
Abstract The application of the digital image correlation technique to the determination of the J‐integral at fracture initiation for carbon black‐filled natural rubber compounds is discussed. Three different compounds with varying carbon black content were tested, using two different test configurations: pure shear and biaxial tensile test. Digital image correlation was used to measure the displacement field around the crack tip in the tested specimens. From the displacement field, which was interpolated using a finite element scheme, the stresses were evaluated by using Ogden's hyperelastic model, and the J‐integral could be calculated. The results compare well with both theoretical and finite element results.